Do Fish Perceive Anaesthetics as Aversive? - Readman, Gareth D.; Owen, Stewart F.; Murrell, Joanna C.; Knowles, Toby G. (PLOS ONE, 2013)
This study addresses a fundamental question in fish welfare: are the anaesthetics used for fish aversive? Despite years of routine general use of many agents, within both scientific research and aquaculture, there is a paucity of information regarding their tolerance and associated behavioural responses by fish. This study examined nine of the most commonly used fish anaesthetic agents, and performed preference tests using adult mixed sex zebrafish (Danio rerio), the most commonly held laboratory fish. Video tracking software quantified swimming behaviour related to aversion for each anaesthetic at 50% of its standard recommended dose compared with clean water in a flow-through chemotaxic choice chamber. Results suggest that several commonly used anaesthetics were aversive, including two of the most commonly recommended and used: MS222 (ethyl 3-aminobenzoate methanesulphate) and benzocaine. For ethical best practice, it is recommended that compounds that are aversive, even at low concentration, should no longer be used routinely for anaesthesia or indeed the first step of humane euthanasia of adult zebrafish. Two agents were found not to induce aversive behavioural responses: etomidate and 2,2,2 tribromoethanol. For the millions of adult zebrafish used in laboratories and breeding worldwide, etomidate appears best suited for future routine humane use.